2020
DOI: 10.20944/preprints202008.0500.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drugs Modulating CD4+ T Cells Blood-Brain Barrier Interaction in Alzheimer's Disease

Abstract: The effect of Alzheimer's disease (AD) medications on CD4+ T cells homing has not been thoroughly investigated. Alzheimer's disturbs the life of at least five million persons in the USA. CD4+ T cells could both exacerbate and reduce AD symptoms. Regulating CD4+ T cells homing to the leaky blood-brain barrier (BBB) constitutes a new hope for enhancing AD prognosis. Alzheimer's drugs such as Donepezil (Aricept), Rivastigmine (Exelon), Galantamine (Razadyne) and memantine are known to play an important part in re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 84 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…CD4+ effector cells can produce autoantibodies against amyloid and therefore harbour protection against amyloid burden. 68 It is thought that genetic drivers of immune-cell profiles may in part explain sex differences observed in response to Alzheimer’s disease pathology. 69 , 70 Thus, it is noteworthy to see an immune-target arise at both the variant-level with GATA3 , and at the whole genome level with our genetic correlation analyses.…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ effector cells can produce autoantibodies against amyloid and therefore harbour protection against amyloid burden. 68 It is thought that genetic drivers of immune-cell profiles may in part explain sex differences observed in response to Alzheimer’s disease pathology. 69 , 70 Thus, it is noteworthy to see an immune-target arise at both the variant-level with GATA3 , and at the whole genome level with our genetic correlation analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in neurological diseases such as Alzheimer's disease and multiple sclerosis suggested that T lymphocytes were closely related to BBB destruction (28,29). Before entering the brain parenchyma, pro-inflammatory CD17+ T cells were interacted closely with vascular endothelial cells by promoting the downregulation of tight junction protein and adhesion protein, stimulating the expression of pro-inflammatory cytokines, and promoting the transmigration of CD4+ T cells (27,28). The infiltrated CD8+ T cells also showed to be involved in BBB destruction through a perforin-dependent process (30).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting topic also is the detection of different isoforms and alternative splicing cases of microglial markers 71 . The effect of drugs on the Interaction between microglia and CD4+ T cells infiltrating the brain during neurodegenerative diseases is another one 72 . These developments could support scRNA‐seq becoming a plausible alternative to classical cellular clustering methods.…”
Section: Discussionmentioning
confidence: 99%